Assessing the pharmacokinetics and toxicology of polymeric micelle conjugated therapeutics. (4th March 2021) - Thotakura, Nagarani; Parashar, Poonam; Raza, Kaisar
ABSTRACT: Introduction : Analogous to nanocarriers such as nanoparticles, liposomes, nano lipoidal carriers, niosomes, and ethosomes, polymeric micelles have gained significance in the field of drug delivery. They have attracted scientists worldwide by their nanometric size, wide range of polymers available for building block synthesis, stability and potential to enhance the targeting and safety of drugs. Incorporation of drugs within the interior of polymeric micelles alters the drug pharmacokinetics, which generally results in increased efficiency. Areas covered : This review deals with the pharmacokinetics of various anti-neoplastic drugs loaded into micelles. The structure of polymeric micelles, polymers employed in their development and techniques involved will be discussed. This is followed by discussion on the pharmacokinetics of anti-cancer drugs loaded into polymeric micelles and the toxicity concerns associated. Expert opinion : Polymeric micelles are nanometeric carriers, with higher stability, polymeric flexibility and higher drug loading of poorly water-soluble drugs. These nanosystems help in increasing the bioavailability of drugs by encapsulating them within the hydrophobic core. The proper selection and design of the amphiphilic polymer for micelles is a crucial step as it decides the toxicity and the biocompatibility.